Analisis Sistem Antrean Layanan Teller - Lismawanti Safitri; Satriyantara, Rio; Irma Risvana Dewi (Mandalika Mathematics and Educations Journal, 2025)
A bank is a financial institution that plays an important role in fulfilling and providing various financial services to customers. The increase in the number of customers and service time leads to queuing, especially at the teller section, thereby affecting waiting times. This article discusses customer queues at the teller service of Bank R in West Nusa Tenggara Province (NTB). Queues arise when service demand exceeds available capacity, causing customers to wait due to limited teller services. This study aims to analyze the optimization of the queuing system at teller services using the Multi-Channel Single-Phase queuing model. This model features multiple entry lines into the service system but only one service facility. The results show that the service intensity level () from Monday to Friday is , , , , and , respectively. Since , the steady-state condition is met. Thus, the queuing system performance can be considered optimal.